Pollutions maritimes des zones côtières – comparaison entre les infractions pénales en matière internationale - Tetley Andrew (VertigO, 2010)
This article addresses the international legal regime underpinning criminal sanctions for pollution incidents from ships. After an overview of the principal legal instruments – MARPOL and UNCLOS – the author considers the national legislation of a select number of countries and offers some conclusions, taking into account the 2005 EU directive on ship pollution.